2015
DOI: 10.1016/j.drugalcdep.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Blunted striatal responses to favorite-food cues in smokers

Abstract: Background Although tobacco-smoking is associated with relatively leaner body mass and smoking cessation with weight gain, the brain mechanisms underlying these relationships are not well understood. Smokers compared to non-smokers have shown diminished neural responses to non-tobacco rewarding stimuli (e.g., monetary rewards), but brain responses to favorite-food cues have not been investigated relative to smoking status. We hypothesized that smokers would exhibit diminished neural responses compared to non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…For example, dependent smokers exhibited equivalently low reward system activity in response to both reward types 14 . An fMRI study revealed that smokers exhibited lower brain reactivity, especially in reward-related brain regions (e.g., caudate and putamen), to nontobacco rewardrelated stimuli (e.g., favorite food) compared with nonsmokers 15 . Another study investigated the association between the severity of nicotine dependence and the response to monetary rewards and found that the intensity of nicotine craving among smokers was linked to lower sensitivity to nondrug-related rewards 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, dependent smokers exhibited equivalently low reward system activity in response to both reward types 14 . An fMRI study revealed that smokers exhibited lower brain reactivity, especially in reward-related brain regions (e.g., caudate and putamen), to nontobacco rewardrelated stimuli (e.g., favorite food) compared with nonsmokers 15 . Another study investigated the association between the severity of nicotine dependence and the response to monetary rewards and found that the intensity of nicotine craving among smokers was linked to lower sensitivity to nondrug-related rewards 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As stressed smokers reported to eat less than usual and stressed nonsmokers reported to eat more than usual, the present findings dovetail with the idea of a "brain reward site competition. " Specifically, a shared neural reward pathway may be "occupied" by a rewarding substance and, thus, individuals tend to consume one rewarding substance to the other's exclusion (Cummings, Ray, & Tomiyama, 2017;Jastreboff et al, 2015;Meule, 2014;Warren & Gold, 2007). That is, smokers seem to retreat to smoking as their favorite drug for coping with stress and are, therefore, "immune" against other substances or behaviors that might serve this function.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking appears to be a primary reinforcer while reinforcing properties of natural rewards such as food are reduced in current smokers. For example, current smokers had reduced activation of reward-related brain areas in response to food cues (Jastreboff et al, 2015) and-in contrast to nonsmokers-showed an approach bias towards smoking-related cues but not towards CONTACT Adrian Meule, PhD adrian.meule@sbg.ac.at Department of Psychology, University of Salzburg, Hellbrunner Straße ,  Salzburg, Austria.…”
Section: Introductionmentioning
confidence: 99%
“…This lower reward sensitivity was not alleviated by nicotine or varenidine (a α4β2 receptor agonist), and was correlated with higher nicotine dependence severity [39]. In another series of studies, smokers showed reduced responsiveness to appetitive rewards compared with nonsmokers, indicated by blunted striatal activation [40] and connectivity [41] in response to favorite-food cues. Blunted neural responses to naturally rewarding stimuli have also been related to craving, smoking abstinence, and treatment outcomes in smokers [4244].…”
Section: Introductionmentioning
confidence: 99%